The Relationship Between Breast Cancer Knowledge and Self-Breast Examination (SBE) Behavior Among Female Students at SMAN 1 Krueng Barona Jaya, Aceh Besar Regency - Farah Sabrina; Yustika Yustika; Nurul Anna (Jurnal Pakar Pengabdian Kesehatan, 2025)
Breast cancer is one of the most common types of cancer in women, including in Indonesia. Early detection of breast cancer can be done through Breast Self-Examination (SADARI), yet the practice of SADARI remains low, especially among teenage girls. This study aims to determine the relationship between breast cancer knowledge and SADARI behavior among female students at SMAN 1 Krueng Barona Jaya, Aceh Besar Regency. This study used a quantitative method with a cross-sectional design. The study sample consisted of 53 respondents selected using total sampling. Data were collected using a questionnaire and analyzed using the Chi-square test. The results showed that most respondents had insufficient knowledge of breast cancer (81.1%) and did not perform SADARI (75.5%). Statistical testing revealed a significant relationship between breast cancer knowledge and SADARI behavior with a p-value of 0.045. The conclusion of this study is that there is a significant relationship between breast cancer knowledge and SADARI behavior among the female students. Increased health education regarding breast cancer and SADARI is greatly needed as an early detection effort.